Aggressive Infection by K1/ST1265 Klebsiella pneumoniae Leading to Multiple Abscesses: Case Report and Literature Review - Chen L; Qiu C; Lu Y; Lin J; Xu L (Infection and Drug Resistance)
Lina Chen,1,2,* Canhu Qiu,1,* Ye Lu,2 Jianqing Lin,1 Liping Xu1 1Department of Critical Care Medicine, Jiangshan People’s Hospital, Quzhou, People’s Republic of China; 2Department of Critical Care Medicine, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianqing Lin; Liping Xu, Email ljq649695@163.com; 18767009393@163.comAbstract: Hypervirulent Klebsiella pneumoniae (hvKp) has attracted increasing attention in recent years. Diabetes and serotype K1 or K2 are risk factors for invasive liver abscess syndrome including liver abscesses and the metastatic complications such as bacteremia, meningitis, endophthalmitis, and necrotizing fasciitis. Simultaneous infections of the liver, lungs, prostate, brain, and eyes are exceedingly rare. In this paper, a 41-year-old male patient who presented with a 4-day history of fever with polydipsia and polyuria and untreated diabetes deteriorated dramatically with sepsis, prostate abscess, lung abscess, liver abscess and intracranial infection as well as endophthalmitis. He was diagnosed with infection by K1/ST1265 hypervirulent Klebsiella pneumoniae and after treatment with antibiotics and abscess drainage, while the patient still passed away. K1/ST1265 hvKp exhibits exceptionally high virulence and invasiveness, necessitating broad awareness and vigilant monitoring.Keywords: Klebsiella pneumoniae, liver abscess, prostate abscess, brain abscess, serotype K1, sequence type 1265